Targeting glioma-associated microglia and macrophages: a new frontier in glioblastoma immunotherapy - Wang, Bingyang; Li, Cong; Gu, Jiatong; Wang, Xiaojie; Xun, Mingjuan; Jiang, Bin; Yan, Jun (Frontiers in Immunology, 2025)
Glioblastoma (GBM), the most aggressive and lethal subtype of glioma, remains therapeutically intractable despite advances in surgical and chemo-radiotherapy interventions. The highly immunosuppressive tumor microenvironment (TME) contributes significantly to treatment resistance and tumor recurrence. Among the predominant immune constituents, glioma-associated microglia and macrophages (GAMs) constitute a major cellular compartment, exerting profound influence on tumor progression, immune evasion, angiogenesis, and therapeutic response. These myeloid populations, derived from both yolk sac–origin microglia and bone marrow–derived macrophages, exhibit remarkable functional plasticity and are actively recruited, polarized, and reprogrammed by tumor-intrinsic and environmental cues. Recent studies have elucidated a range of molecular pathways, including chemokine signaling, metabolic reprogramming, and epigenetic modulation, that govern GAM behavior and sustain their tumor-supportive phenotype. Therapeutic strategies targeting GAM recruitment, depletion, or functional re-education toward an anti-tumor state are emerging as promising adjuncts to conventional and immune-based therapies. This review comprehensively explores the ontogeny, regulatory networks, and pathological roles of GAMs in GBM, with particular emphasis on novel immunotherapeutic approaches, including CSF-1R blockade, nanoparticle-mediated reprogramming, and oncolytic virotherapy. A deeper understanding of GAM–TME interactions will be critical to overcoming immunotherapy resistance and advancing precision immunomodulation in GBM.